Toxigenic fungi and contamination by AFB1 in Algerian traditional foods markets - Ammar-Rachad Medjdoub; Abdellah Moussaoui; Houcine Benmehdi (European Journal of Biological Research, 2023)
This work focused on the realization of a mycological and mycotoxicological study of certain foods manufactured in a traditional way (couscous and spice of Capsicum annuum known locally under the name of sweet hror) and marketed in the city of Bechar. The physico-chemical analyzes revealed that all the samples were poorly hydrated where the average values ​​of relative humidity ranged between 7.23% and 13.58%. For the pH, the values ​​varied between 5.22 and 6.95. The enumeration of the fungal flora indicated that the couscous samples (coarse and fine) represented a contamination rate of 2.92*102 and 1.71*102 CFU/g respectively. While, the sweet hror samples represented a higher contamination rate (4.68*102 CFU/g), with a clear dominance of the genera of Aspergillus (46.42%) and Penicillium (26.28%). Otherwise, the mycotoxicological analysis showed us that 78.55% of the Aspergillus isolates of the group (flavus-parasiticus) tested were producers of aflatoxins (B1 and G1) and that 86.66% of the isolates of A. ochraceus and 40% of Penicillium species, were ochratoxin A producers. In addition, the detection of mycotoxins at the sample level revealed that 63.63% of couscous samples were contaminated with mycotoxins. While sweet hror was the most contaminated (78.57%). Furthermore, the quantification of AFB1 by HPLC-FLD for 4 samples of sweet hror revealed only one contaminated sample (21.75 µg/kg). Generally, it can be admitted that the rate of contamination by AFB1 was too high, which can be considered a real risk to human health.